2023
DOI: 10.1073/pnas.2221324120
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of coronavirus frameshifting elements: Competing stem networks explain conservation and variability

Shuting Yan,
Qiyao Zhu,
Jenna Hohl
et al.

Abstract: The frameshifting RNA element (FSE) in coronaviruses (CoVs) regulates the programmed −1 ribosomal frameshift (−1 PRF) mechanism common to many viruses. The FSE is of particular interest as a promising drug candidate. Its associated pseudoknot or stem loop structure is thought to play a large role in frameshifting and thus viral protein production. To investigate the FSE structural evolution, we use our graph theory-based methods for representing RNA secondary structures in the RNA-As-Graphs (RAG) framework to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 58 publications
1
15
0
Order By: Relevance
“…These data are also consistent with other groups’ analyses of the FSE secondary structure (Lan et al 2022; Pekarek et al 2023; Yan et al 2022; Rangan et al 2021; Schlick, Zhu, Dey, et al 2021). We have emphasized in our prior work that not only can the RNA fold into different conformations for the same length (Schlick, Zhu, Dey, et al 2021; Yan et al 2023; Schlick, Zhu, Jain, et al 2021); the fold distribution is also highly sensitive to length, when residues are either added or deleted (Yan et al 2023) .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…These data are also consistent with other groups’ analyses of the FSE secondary structure (Lan et al 2022; Pekarek et al 2023; Yan et al 2022; Rangan et al 2021; Schlick, Zhu, Dey, et al 2021). We have emphasized in our prior work that not only can the RNA fold into different conformations for the same length (Schlick, Zhu, Dey, et al 2021; Yan et al 2023; Schlick, Zhu, Jain, et al 2021); the fold distribution is also highly sensitive to length, when residues are either added or deleted (Yan et al 2023) .…”
Section: Resultsmentioning
confidence: 99%
“…As a control we also DMS probed, modeled, and measured the frameshifting efficiency of two additional longer WT constructs (156nt and 222nt long) (Figures 4A, B, and C, respectively). Our previous work has shown that longer constructs of SARS-CoV-2 FSE tend to adopt other conformations due to a competing Stem 1 and attenuator hairpin (Yan et al 2022; Yan et al 2023) (S. lee, S. Yan, A. Dey et al, Pers. comm., 2024).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Among viral RNA structures, previous comparisons, conducted by NMR or X-ray crystallography, were limited to the comparison of two mutants (67) or two homologs (68)(69)(70). Structural comparisons for coronavirus RNA genomes have been limited to RNA secondary structure, including analysis of the 5' UTR (47,57) and the frameshift stimulation element (71), rather than comparisons of tertiary structure. Cryogenic electron microscopy (cryo-EM) offers the possibility of more routinely characterizing RNA elements across multiple homologs, particularly when integrated with biochemical secondary structure determination and automated computer modeling, such as in the Ribosolve pipeline (72).…”
Section: Introductionmentioning
confidence: 99%
“…8 A pseudoknot structure is a structure motif of nucleic acids that has two (or more) stem-loops; in a basic pseudoknot structure, one stem is nested into the loop region of the other stem-loop. Pseudoknot structures were found in structured RNAs involved in important biological processes, such as the frameshift element of viruses, 13,14 the telomerase RNA component, 15 and tRNAlike structures. 16 Nonstructural proteins (nsp)7−16, which are coded in the ORF1ab gene at the 5′ terminus of the genome, play primary roles in replicating the virus genome.…”
mentioning
confidence: 99%